AMPK promotes induction of the tumor suppressor FLCN through activation of TFEB independently of mTOR. Issue 11 (19th August 2019) - Collodet, Caterina; Foretz, Marc; Deak, Maria; Bultot, Laurent; Metairon, Sylviane; Viollet, Benoit; Lefebvre, Gregory; Raymond, Frederic; Parisi, Alice; Civiletto, Gabriele; Gut, Philipp; Descombes, Patrick; et al.
Abstract : AMPK is a central regulator of energy homeostasis. AMPK not only elicits acute metabolic responses but also promotes metabolic reprogramming and adaptations in the long‐term through regulation of specific transcription factors and coactivators. We performed a whole‐genome transcriptome profiling in wild‐type (WT) and AMPK‐deficient mouse embryonic fibroblasts (MEFs) and primary hepatocytes that had been treated with 2 distinct classes of small‐molecule AMPK activators. We identified unique compound‐dependent gene expression signatures and several AMPK‐regulated genes, including folliculin (Flcn), which encodes the tumor suppressor FLCN. Bioinformatics analysis highlighted the lysosomal pathway and the associated transcription factor EB (TFEB) as a key transcriptional mediator responsible for AMPK responses. AMPK‐induced Flcn expression was abolished in MEFs lacking TFEB and transcription factor E3, 2 transcription factors with partially redundant function; additionally, the promoter activity of Flcn was profoundly reduced when its putative TFEB‐binding site was mutated. The AMPK‐TFEB‐FLCN axis is conserved across species; swimming exercise in WT zebrafish induced Flcn expression in muscle, which was significantly reduced in AMPK‐deficient zebrafish. Mechanistically, we have found that AMPK promotes dephosphorylation and nuclear localization of TFEB independently of mammalian target of rapamycin activity. Collectively, we identified the novel AMPK‐TFEB‐FLCN axis, which may function as a key cascade for cellular and metabolic adaptations.—Collodet, C., Foretz, M., Deak, M., Bultot, L., Metairon, S., Viollet, B., Lefebvre, G., Raymond, F., Parisi, A., Civiletto, G., Gut, P., Descombes, P., Sakamoto, K. AMPK promotes induction of the tumor suppressor FLCN through activation of TFEB independently of mTOR. FASEB J. 33, 12374–12391 (2019). www.fasebj.org